Effect of Metabolites of Lactobacillus Strains on Clinical Isolates of the Human Intestinal Microbiota - Ivashko, M.V.; Boyko, N.V.; Івашко, М.В.; Бойко, Н.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Currently, most clinically effective pharmabiotics are based on bacterial strains of the genus Lactobacillus. The antimicrobial properties of these microorganisms are attributed to their unique ability to synthesize metabolites that have significant potential in combating pathogenic microorganisms. The aim of this work was to study the effect of the metabolites of six probiotic Lactobacillus strains in vitro on opportunistic and commensal representatives of the human gut microbiota. Methods. Metabolites were isolated from six proprietary probiotic Lactobacillus strains (Lactobacillus plantarum A, L. bulgaricus A6, L. bulgaricus A22, L. bulgaricus S6, L. bulgaricus S19, and L. rhamnosus S25) by filtering the supernatant using syringe cellulose acetate membrane nanofilters with a pore diameter of 0.22 μm. The effect of the metabolites was evaluated against opportunistic (Escherichia coli, Enterobacter cloacae, Proteus mirabilis, Bacillus cereus, and Staphylococcus aureus) and commensal (Enterococcus faecalis, L. plantarum) intestinal microbiota strains. Cultures were performed on agarized selective and differential diagnostic nutrient media. Microsoft Office Excel software was used for statistical processing of the experimental results. Results. Our study has shown that the metabolites of L. plantarum A, L. bulgaricus A6, L. bulgaricus S19, and L. rhamnosus S25 strains are characterized by the maximum ability to suppress the growth of E. coli, lac - on Day 1 of co-cultivation. Already on Day 2, the metabolites of L. plantarum A strain completely inhibited the growth of E. coli, lac -. The metabolites of probiotic L. bulgaricus A22 and L. bulgaricus S19 strains inhibited the growth of E. coli, lac - on Day 2 slightly less effectively. On Day 1 of co-cultivation, the metabolites of L. bulgaricus A6, L. bulgaricus A22, L. bulgaricus S6, and L. rhamnosus S25 strains showed the highest inhibitory effect on E. cloacae. However, on Day 2, the metabolites of L. plantarum A strain were the most effective, completely inhibiting the growth of E. cloacae. According to the study results, the metabolites of L. bulgaricus A6, L. bulgaricus A22, and L. bulgaricus S19 strains showed the best antagonistic effect on P. mirabilis. On Day 2 of co-cultivation, the metabolites of L. plantarum A strain completely inhibited the growth of P. mirabilis. The metabolites of L. bulgaricus A22, L. bulgaricus S6, L. bulgaricus S19, and L. rhamnosus S25 strains also showed an antagonistic effect on P. mirabilis on Day 2, but to a lesser degree. After 24 h, the metabolites of L. bulgaricus S19 and L. rhamnosus S25 strains turned out to be the most effective toward B. cereus. However, after 48 h of co-cultivation, it was the metabolites of L. plantarum A strain that demonstrated the best inhibitory properties, while the metabolites of L. bulgaricus S6 and L. bulgaricus S19 strains showed less efficacy. When studying the properties of the metabolites of probiotic Lactobacillus strains in relation to commensal representatives of the human gastrointestinal tract (E. faecalis and L. plantarum), in most cases, we noted no inhibition of commensal bacteria growth. In some cases, the addition of metabolites into the nutrient medium during the cultivation of E. faecalis and L. plantarum was noted to stimulate the growth of the latter. On Day 1 of co-cultivation, the metabolites of L. plantarum A, L. bulgaricus A6, L. bulgaricus S19, and L. rhamnosus S25 strains did not inhibit the growth of E. faecalis. However, on Day 2, it was found that the metabolites of L. plantarum A and L. bulgaricus A6 strains showed a stimulating effect on this test strain. On Day 1 of cultivation, the metabolites of strain L. bulgaricus S19 showed a stimulating effect on L. plantarum. On Day 2, the metabolites of strain L. bulgaricus S6 were the most effective, also demonstrating a stimulating effect. Conclusions. We anticipate the potential application of metabolites from the probiotic Lactobacillus strains for personalized modification of the human microbiome, which is particularly important in the context of advanced approaches to the modern 3P medicine.